Seres vivos: fuente de inspiración para el diseño artificial - Fredy Hernán Martínez Sarmiento; Alberto Delgado R. (Tecnura, 2013)
Many of the “intelligent” features that we want in robots, machines and man-made systems, are already well implemented by nature. Therefore, it is reasonable to expect that, by imitating nature, "intelligent solutions" to human problems can be found. In this paper, we present a survey on the analysis of current developments connected to artificial design inspired by nature. Particular interest is devoted to living organisms. The study takes the POE model as the starting point, establishing a three-dimensional framework with three axes of biological development, namely phylogenetic, ontogenetic and epigenetic axes. For each of these axes, a survey of existing hardware implementations is conducted in order to gather their characteristics, strengths and weaknesses and establish a general map of the latest technological developments. Finally, we conclude that implementing this type of nature inspired algorithms is not only important but also indispensable in solving many complex problems today.